Focus control using flexible lens - Abdullah, Soran Jalal; Khan, Md. Raisuddin; Wahyudi, Martono (2005)
Traditional focusing system usually uses multilenses by moving two concentric lenses towards or away from each other. However, the small and compact implementation using multiple-lenses is difficult to achieve since a certain distance between two- lenses is required for different focal length. To overcome this problem, in this paper, a new focusing system based on flexible lens is introduced. The flexible lens is made from natural rubber membrane and water, which is used as the optical medium. In the proposed system, focusing is achieved by the change of volume of water inside the lens. A passive control algorithm for auto-focusing has been employed using LabVIEW, a graphical programming language. The experiments show that the proposed flexible lens is capable of projecting colored images onto the CCD sensor for objects lying at a distance of 100 mm to 7000 mm from the camera.